2020
DOI: 10.1016/j.mtla.2020.100719
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and athermal contributions to the flow stress of martensite

Abstract: Recent theories consider as-quenched martensite as a composite which strain hardens by the gradual yielding of constituents. An underlying hypothesis is that hardening comes primarily from athermal hardening contributions. In this contribution, we conducted strain-rate jump and tension-compression tests to quantify the athermal and kinematic hardening contributions in martensite. It is shown that athermal hardening accounts for ~75% of the total strength of as-quenched martensite. The magnitudes of athermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…based on an inverse analysis from the macroscopic mechanical behavior. It was shown that microstructural heterogeneities (dislocation densities, lath sizes, carbon segregations) as well as internal stresses resulting from the transformation deformation must be taken into account to explain the unique behavior of these steels [50]. The density of dislocations appears to be a major contribution explaining almost one half of the stress distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…based on an inverse analysis from the macroscopic mechanical behavior. It was shown that microstructural heterogeneities (dislocation densities, lath sizes, carbon segregations) as well as internal stresses resulting from the transformation deformation must be taken into account to explain the unique behavior of these steels [50]. The density of dislocations appears to be a major contribution explaining almost one half of the stress distribution.…”
Section: Resultsmentioning
confidence: 99%
“…in the martensite is originated by the microstructure principally (laths sizes, dislocations densities); internal stresses contribute to the phenomenon without being the only explanation as reported by Wang et al [50]. The functional form for the local yield stress spectrum in the CCA model (an Avrami type law [2]) can be selected differently based on the type of distribution found experimentally.…”
Section: Dislocations and Strength Of Austenitementioning
confidence: 99%
“…Long-range dislocation interactions contribute to the athermal component of flow stress, while the thermal component of flow stress arises from short-range dislocation obstacles, such as the Peierls-Nabarro stress and dislocation forests [7,33]. Wang et al recently quantified the athermal and thermal components of flow stress in quenched and tempered steels [65]. For a steel similar in chemical composition (0.25C-2.42Mn-1.44Si-0.01Al mass%) to the current work that was quenched and then tempered at 400 • C for 5 min, the athermal component accounted for approximately 75% of flow stress [65].…”
Section: Correlation Of Tensile Mechanical Properties With Microstrucmentioning
confidence: 99%
“…Wang et al recently quantified the athermal and thermal components of flow stress in quenched and tempered steels [65]. For a steel similar in chemical composition (0.25C-2.42Mn-1.44Si-0.01Al mass%) to the current work that was quenched and then tempered at 400 • C for 5 min, the athermal component accounted for approximately 75% of flow stress [65]. For QP3Mn, temperature-sensitive short-range dislocation barriers do not appear to have a significant impact on flow stress for two reasons: (1) their contribution to flow stress is very small compared with long-range barriers, and (2) the test temperature range is small (i.e., approximately 95 • C), which amounts to a small increase in the thermally dependent component of flow stress.…”
Section: Correlation Of Tensile Mechanical Properties With Microstrucmentioning
confidence: 99%
“…≤400 °C ) but Al is more effective at high tempering temperature and longer tempering times [35]. However, Bauschinger test results from Wang et al showed that kinematic hardening accounts for a large proportion of the flow stress in tempered martensite and Si is more effective than Al in resisting the reduction in kinematic hardening for all tempering conditions between 300 °C and 600 °C [37].…”
Section: Introductionmentioning
confidence: 99%